2020
DOI: 10.1124/mol.119.119339
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Level Characterization of the Methadone-Stabilized Active Conformation of µ-Opioid Receptor

Abstract: Methadone is a synthetic opioid agonist with notoriously unique properties, such as lower abuse liability and induced relief of withdrawal symptoms and drug cravings, despite acting on the same opioid receptors triggered by classical opioids, in particular the µ-opioid receptor (MOR). Its distinct pharmacologic properties, which have recently been attributed to the preferential activation of β-arrestin over G proteins, make methadone a standard-of-care maintenance medication for opioid addiction. Although a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…Moreover, morphine displayed several interactions with helix 6, which were mainly missing for methadone and fentanyl, also consistent with previous findings (Kapoor et al, 2020;Lipiński et al, 2019). The observed binding pose for methadone indicated a salt bridge with D147 3.32 as only direct interaction, comparable to the findings of Kapoor et al For fentanyl, we identified an H-bond with Y326 7.43 as critically important interaction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, morphine displayed several interactions with helix 6, which were mainly missing for methadone and fentanyl, also consistent with previous findings (Kapoor et al, 2020;Lipiński et al, 2019). The observed binding pose for methadone indicated a salt bridge with D147 3.32 as only direct interaction, comparable to the findings of Kapoor et al For fentanyl, we identified an H-bond with Y326 7.43 as critically important interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we were able to identify important regions in the receptor which we correlated with the voltage effect on the MOR. Specifically, our molecular docking studies and subsequent fingerprint analysis, which calculated the interactions between a ligand and a receptor, revealed that morphine (or agonists with the morphinan scaffold) interacted with D147 3.32 , Y148 3.33 and the water networks between Y148 3.33 and H297 6.52 as described before (Huang et al, 2015;Kapoor et al, 2020;Lipiński et al, 2019;Vo et al, 2021).…”
Section: Discussionmentioning
confidence: 73%
“…In recent years, high-resolution structures of the MOR have been acquired by both x-ray crystallography [14] , [15] and cryo-electron microscopy (cryo-EM) [16] , for an inactive conformation of the receptor bound with a morphinan antagonist, β-FNA [15] , and active conformations bound with agonists BU72 and DAMGO [14] , [16] . These structures have been leveraged to investigate the binding mechanisms, and related MOR conformations, of the opioids having therapeutic implications, such as methadone, morphine, and TRV130 [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…One possibility that could explain bias is that agonists allow receptors to sample distinct sets of conformational spaces which correlate with specific effectors and signaling pathways. Kapoor et al use Molecular Dynamics simulations to predict the conformational dynamics of the mu opioid receptor bound to methadone in comparison to morphine and a G protein-biased ligand, as useful tools to navigate these conformational spaces (Kapoor et al, 2020).…”
Section: Significance Statementmentioning
confidence: 99%